A quantitative analysis of overspray in Aerosol Jet® printing. (27th October 2021) - Feng, James Q; Ramm, Alex; Renn, Michael J
Abstract: As Aerosol Jet® (AJ) printing is becoming more attractive to additive manufacturing, printed electronics, among other applications, reducing or minimizing the amount of ink droplets landing in unintended regions—known as the overspray—has been elevated on the agenda for print quality control and improvement. Many AJ users had discussed the overspray issue associated with AJ printing, while the metrology for quantified evaluation of overspray is still lacking. In this work, the likely physical mechanism for inducing overspray is analyzed along with a set of computational fluid dynamics (CFD) simulations. We then present a 2D image processing method for quantitatively evaluating the severity of overspray in terms of its percent area coverage versus a normalized distance from printed line edge. Our results show that the amount of overspray of AJ printing seems to scale with the printed line width (LW), and usually to become negligible (e.g. percent area coverage of overspray < 1%) beyond 30%–40% of LW from line edges. The overspray is shown to often decrease by increasing the jet velocity and sheath-to-mist ratio. Without loss of generality and for concise illustration, herewith we use only one representative ink to print test samples for the quantitative overspray analysis. The results have been found to bear a resemblance to AJ printed features with many other inks.